2009
DOI: 10.1211/jpp.61.10.0009
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic index of methotrexate depends on circadian cycling of tumour necrosis factor-α in collagen-induced arthritic rats and mice

Abstract: Our findings suggest that choosing an optimal dosing time associated with the 24-h cycling of TNF-alpha could lead to effective treatment of rheumatoid arthritis by methotrexate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 27 publications
4
26
1
Order By: Relevance
“…RA chronotherapy has been studied using glucocorticoid and benoxaprofen (16 -18). We also revealed that optimizing the dosing time of methotrexate, which is a disease-modifying antirheumatic drug that has been used to treat many RA patients, improved the symptoms of RA compared to the current standard dosing methods (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…RA chronotherapy has been studied using glucocorticoid and benoxaprofen (16 -18). We also revealed that optimizing the dosing time of methotrexate, which is a disease-modifying antirheumatic drug that has been used to treat many RA patients, improved the symptoms of RA compared to the current standard dosing methods (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the arthritis scores of the ZT10 group did not significantly differ from those of the control group for the entire study period in mice. 26 In our previous studies using CIA model, MTX dosing groups showed no significant adverse effects such as myelosuppression. MTX is an anticancer drug, the administration of which is often associated with adverse effects such as myelosuppression.…”
Section: Disease-modifying Antirheumatic Drugs Methotrexatementioning
confidence: 79%
“…25 A previous study administered MTX once daily at Zeitgeber time (ZT) 10 or ZT22 and found that the arthritis score was significantly lower in the ZT22 group than in the control and ZT10 groups in rats with CIA ( Figure 1). 26 On day 22, the inhibition rate of the arthritis score in the ZT22 group was approximately fivefold higher than that in the ZT10 group. Moreover, plasma TNF-α levels were found to be 3.03-to 5.39-fold higher in mice with CIA than in normal mice at all sampling times after the onset of RA.…”
Section: Disease-modifying Antirheumatic Drugs Methotrexatementioning
confidence: 85%
“…In previous studies, we revealed that the circadian rhythms of SAA and TNF- levels, which peak in the light phase, were maintained after RA onset in CIA and MRL/lpr mice ( Fig. 6 and 9; To et al, 2009 and2011). Based on the circadian rhythms of plasma SAA and TNF- levels in MRL/lpr mice (Fig.…”
Section: Basic Studymentioning
confidence: 83%
“…In the CIA model, clear circadian rhythms in SAA and TNF-levels were observed, with higher levels seen in the morning and lower levels observed at night ( Fig. 6; To et al, 2009), and MTX was intraperitoneally injected at 5:00 or 17:00 every 7 days for 3 weeks. The 5:00-treated group displayed significantly reduced arthritis scores compared with the control and 17:00-treated groups (P < 0.01, respectively; Fig.…”
Section: Basic Studymentioning
confidence: 95%